HYDROLYSIS KINETIC MODEL OF SWEET POTATO USING ENDOGENOUS AMYLASE ENZYME - Anandhavardhini, Anindita
The sugar consumed by the Indonesian people comes from domestic production and imports. However, the sugar consumption of the Indonesian people from year to year has increased so that Indonesia needs a higher number of imports to fulfill the needs of national sugar consumption. Sweet potato contains starch which can undergo enzymatic hydrolysis reaction by utilizing endogenous enzymes to produce maltose syrup. The need for enzymes in the starch hydrolysis process can be quantified based on modeling, so that it can describe the potential of endogenous ????-amylase enzymes in the hydrolysis process of sweet potato starch and identify activities that may occur during the hydrolysis process. Therefore, this study aims to perform a modeling based on the hydrolysis of sweet potato starch using endogenous and exogenous beta-amylase enzymes. The scope of this research refers to the research of Lohoo and Tirtaadji (2020) regarding the hydrolysis of sweet potato starch using the endogenous beta-amylase enzyme. The amount of reducing sugar was determined using the Nelson-Somogyi method. The modeling was carried out using Matlab software with the nonlinear least square method (lsqnonlin) and Michaelis Menten as a kinetic model of starch hydrolysis enzymatically. The results of the research conducted to determine that the hydrolysis reaction with exogenous enzymes produces a reaction rate that is twice as fast as the utilization of endogenous enzymes. The products of hydrolysis with endogenous beta-amylase enzymes can reduce the need for exogenous beta-amylase enzymes as much as 54.56%.